Higher Territorial Units and Transportation Accessibility of their Centers - Janacek, Jaroslav; Janosikova, Ludmila (Communications - Scientific Letters of the University of Zilina, 2002)
The paper deals with administration partition of Slovakia in terms of transportation accessibility of higher territorial unit centers. Transportation accessibility is defined as an average distance, which has to be traveled by an inhabitant from his place of residence to the nearest higher territorial unit center. Transport-optimal partition is compared to designs, in which the place of residence of some higher territorial unit center is set beforehand.
Keywords: no keywords